2021
DOI: 10.1093/jxb/erab487
|View full text |Cite
|
Sign up to set email alerts
|

Volatile-mediated plant–plant interactions: volatile organic compounds as modulators of receiver plant defence, growth, and reproduction

Abstract: It is firmly established that plants respond to biotic and abiotic stimuli by emitting volatile organic compounds (VOCs). These VOCs provide information on the physiological status of the emitter plant and are available for detection by the whole community. In the context of plant-plant interactions, research has focused mostly on defence-related responses of receiver plants. However, responses may span hormone signalling, both primary and secondary metabolism and ultimately affect plant fitness. Here we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 145 publications
2
81
1
Order By: Relevance
“…A key observation in the present study was reduced herbivore-damage to Scots pine saplings that had been exposed to HIPVs, which is indicative of a gain in resistance. The underlying mechanism for this ecological effect is probably related to induced or primed defence responses [ 15 , 23 , 60 ]. VOCs are an important component of pine defence; they are toxic to bark beetles at high vapour concentrations, which has been shown to inhibit their feeding activity [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key observation in the present study was reduced herbivore-damage to Scots pine saplings that had been exposed to HIPVs, which is indicative of a gain in resistance. The underlying mechanism for this ecological effect is probably related to induced or primed defence responses [ 15 , 23 , 60 ]. VOCs are an important component of pine defence; they are toxic to bark beetles at high vapour concentrations, which has been shown to inhibit their feeding activity [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the production of defensive VOCs, a greater photosynthesis rate is expected to provide more resources for other C-based defensive chemicals, physical barriers and compensatory growth [ 4 , 60 , 63 ]. A physical structure related to the defensive chemistry of Scots pine is the RD, tube-like structures formed by secretory ECs that produce and exude terpenoid resin into the lumen [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prepare for the incoming pathogens, primed plants usually undergo metabolic changes in the biosynthesis of primary and secondary metabolites (Frost et al, 2008;War et al, 2011;Brosset and Blande, 2022). It was recently demonstrated that BABA treatment induced resistance to Botrytis cinerea and affected the contents of soluble sugar and phenylpropanoid metabolites in grape berries (Li et al, 2021a).…”
Section: Physiological Transcriptional and Metabolic Changes During P...mentioning
confidence: 99%
“…Monoterpene emission stimulated by MeJA treatment was strongly attenuated by simultaneous drought stress at both sampling times. Reduction in monoterpene emission should decrease the ability of P. glauca to defend itself with volatiles either as direct or indirect defenses or to communicate with volatiles as internal signals as in angiosperm [ 55 , 56 ] to alert other parts of the tree to herbivore attack. This might reflect a reduced priority for anti-herbivore defense responses under an abiotic stress like drought.…”
Section: Discussionmentioning
confidence: 99%